2023
DOI: 10.3389/fbioe.2023.1199230
|View full text |Cite
|
Sign up to set email alerts
|

Lung inflammation perturbation by engineered nanoparticles

Abstract: In recent years, the unique and diverse physicochemical properties of nanoparticles have brought about their wide use in many fields; however, it is necessary to better understand the possible human health risks caused by their release in the environment. Although the adverse health effects of nanoparticles have been proposed and are still being clarified, their effects on lung health have not been fully studied. In this review, we focus on the latest research progress on the pulmonary toxic effects of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 101 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Therefore, this finding allowed us to speculate that FNP1 nanoparticles do not cause significant aggregation and thus reduce the potential to cause nanoparticle‐induced lung inflammation – as previously reported for a range of other nanoparticle vectors. [ 40 ] Also, degradation of the bidentate 89 Zr─O bonds of the polymer coating was observed, however, this can be explained by the stronger osteophillic properties of the 89 Zr 4+ metal cation in vivo, resulting in skeletal remineralization in active bone and joints. [ 41 ] Brant et al explain the polymer complex, in the absence of an octadentate chelating agent, has an incomplete co‐ordination sphere of the radiometal, leading to unfavorable and unspecific bone uptake of the osteophillic radiometal and is not reflective of the nanoparticle behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this finding allowed us to speculate that FNP1 nanoparticles do not cause significant aggregation and thus reduce the potential to cause nanoparticle‐induced lung inflammation – as previously reported for a range of other nanoparticle vectors. [ 40 ] Also, degradation of the bidentate 89 Zr─O bonds of the polymer coating was observed, however, this can be explained by the stronger osteophillic properties of the 89 Zr 4+ metal cation in vivo, resulting in skeletal remineralization in active bone and joints. [ 41 ] Brant et al explain the polymer complex, in the absence of an octadentate chelating agent, has an incomplete co‐ordination sphere of the radiometal, leading to unfavorable and unspecific bone uptake of the osteophillic radiometal and is not reflective of the nanoparticle behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nanostructured MDs, in particular through the release of nanoparticles, can lead in principle to a number of adverse health effects. Of these, lung toxicity of nanoparticles shed by such devices should be considered [11]: Pulmonary toxic ef-fects of nanoparticles and their disturbance of the pulmonary inflammatory response are being recognized as relevant problems. In vivo studies have shown that carbon-based nanoparticles, metal-based nanoparticles, oxide-based nanoparticles, and sulfide-based nanoparticles cause a pulmonary inflammatory response in mice or rats after respiratory exposure.…”
Section: Potential Health Effects Associated With Nanomaterialsmentioning
confidence: 99%